2011
DOI: 10.1073/pnas.1114496108
|View full text |Cite
|
Sign up to set email alerts
|

Structural evidence for the rare tautomer hypothesis of spontaneous mutagenesis

Abstract: Even though high-fidelity polymerases copy DNA with remarkable accuracy, some base-pair mismatches are incorporated at low frequency, leading to spontaneous mutagenesis. Using high-resolution X-ray crystallographic analysis of a DNA polymerase that catalyzes replication in crystals, we observe that a C•A mismatch can mimic the shape of cognate base pairs at the site of incorporation. This shape mimicry enables the mismatch to evade the error detection mechanisms of the polymerase, which would normally either p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
279
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(294 citation statements)
references
References 51 publications
12
279
1
2
Order By: Relevance
“…Our model choice results together with the unimodally distributed Ti/Tv estimates for ALs (and AE loci as well) suggest that these loci largely evolved via a simple mechanism that gives rise to a transition bias (Wakeley 1996). This finding is significant because it provides evidence in support of the long-standing "rare tautomer hypothesis" by Watson and Crick (1953), which holds that spontaneous base substitutions, which are specifically transitions, arise via incorporation of rare base tautomers during DNA replication (Harris et al 2003;Wang et al 2011). …”
Section: Dna Substitution Patterns In Neutral Locisupporting
confidence: 56%
“…Our model choice results together with the unimodally distributed Ti/Tv estimates for ALs (and AE loci as well) suggest that these loci largely evolved via a simple mechanism that gives rise to a transition bias (Wakeley 1996). This finding is significant because it provides evidence in support of the long-standing "rare tautomer hypothesis" by Watson and Crick (1953), which holds that spontaneous base substitutions, which are specifically transitions, arise via incorporation of rare base tautomers during DNA replication (Harris et al 2003;Wang et al 2011). …”
Section: Dna Substitution Patterns In Neutral Locisupporting
confidence: 56%
“…Decades later, it is well established that the replicative and translational machineries form a tight grip around the WC geometry to discriminate against mismatches 25 . There is also evidence that both tautomeric 613 (Fig. 1b) and anionic 79,14,15 (Fig.…”
mentioning
confidence: 85%
“…4a) is required for misincorporation following initial dNTP binding in a wobble conformation, it could provide a mechanism for lowering k pol incorrect relative to k pol correct . Indeed, prior studies have shown that DNA polymerases cannot undergo the necessary conformational changes needed for catalysis when dG•dT is in a wobble conformation 7 and all available structures of catalytically active polymerases with bound mismatches within the active site feature WC-like dG•dT or dA•dC geometries 6,7 . Similarly, WC-like rG•rU mismatches have been shown to form in the first and second codon positions of catalytically active ribosomes 9 , in which wobbles are typically rejected 5 , potentially helping to explain translational error hotspots 41 .…”
Section: Tautomerization/ionization During Misincorporationmentioning
confidence: 99%
See 2 more Smart Citations